Immunotherapeutic effect of adenovirus encoding antimicrobial peptides in experimental pulmonary tuberculosis. Issue 5 (8th March 2021) - Ramos-Espinosa, Octavio; Mata-Espinosa, Dulce; Francisco-Cruz, Alejandro; López-Torres, Manuel Othoniel; Hernández-Bazán, Sujhey; Barrios-Payán, Jorge; Marquina-Castillo, Brenda; Carretero, Marta; del Río, Marcela; Hernández-Pando, Rogelio
Abstract: As components of the innate immune response, antimicrobial peptides (AMPs) efficiently contribute to infection control and maintenance of a latent state in pulmonary tuberculosis (TB). As a therapeutic strategy, the administration of recombinant AMPs could be limited by enzymatic degradation and high production costs. Likewise, strategies based on the induction of AMPs have generated controversial results. In this study, 2 recombinant type-5 adenoviruses (Ad) expressing the human β-defensin 3 (HβD3) or cathelicidin (LL37) were assessed in a murine pulmonary TB model. Mice infected with either a high dose of a drug-sensitive (H37Rv) or a multidrug-resistant (MDR) strain of Mycobacterium tuberculosis ( Mtb ) were treated with a single administration of AdHβD3, AdLL37, AdGFP (control vector expressing a green fluorescent protein), or saline solution (SS). Lungs were obtained to determine the bacterial burden, histologic damage, and cytokine expression at different time points. Mice treated with AdHβD3 or AdLL37 showed significantly lower bacterial load and pneumonia, and higher proinflammatory cytokine expression than the control groups AdGFP and SS. A synergistic therapeutic effect could be observed when first- or second-line antibiotics (ABs) were administered with adenoviral therapy in animals infected with H37Rv or MDR strains, respectively. Adenovirus-delivered AMP's administration constitutes a promising adjuvant therapy for current anti-TB drugs by enhancing a protective immune response and potentially reducing current AB regimes' duration. Graphical Abstract: Adenovirus-delivered antimicrobial peptide administration constitutes a promising adjuvant therapy for current anti-TB drugs by enhancing a protective immune response and potentially reducing current antibiotic regimes' duration.